NusA protein is necessary and sufficient in vitro for phage lambda N gene product to suppress a rho-independent terminator placed downstream of nutL. - Whalen, W (1988)
Transcription antitermination by phage lambda N protein is reproduced in vitro solely with purified components. We have placed a strong rho-independent terminator, lambda tR', in the PL operon about 200 base pairs downstream from the N-recognition site, nutL, and have monitored terminated and run-off transcripts produced by single-round transcription of linear plasmids. In the presence of NusA, one of several host factors implicated in antitermination, N is found to virtually abolish termination at tR'. N is unable to suppress termination if the terminator is preceded by a defective nut site. Thus, during transcription through the nut site, N and NusA can modify RNA polymerase to a termination-resistant form in the absence of any other accessory factor.